Optimal choice of contracting methods: negotiated versus competitive underwritings revisited - Logue, Dennis E; Tiniç, Seha M (Journal of Financial Economics, 1999)
We use a previously unexploited data base, specifically debt offerings by AT\ &T and its subsidiaries in the period 1970–1974, to examine the relative costliness of competitive and negotiated offerings. A sample based on the experience of a single issuer allows us to minimize the influence of agency considerations and differential riskiness of the issuers. We find no systematic ex post cost difference, and we also find that negotiation was chosen during comparatively unsettled times.